TALKING STICK LEARNING MODEL BY ANIMATION VIDEOS IN SOCIAL SCIENCES SUBJECTS - Ayuni, Dewi; Gimin; Rizka, Mifta (International Journal of Educational Best Practices, 2023)
The purpose of this study was to find out the application of the talking stick learning model assisted by video animation can improve student learning outcomes in social studies lessons. Data collection was carried out in class VII B with 32 students. This research is quantitative research with a quasi-experimental approach with a one group pretest-posttest design. Data collection techniques used in the form of observation and tests. The instrument in this study used a learning implementation sheet and 10 multiple choice questions. Data analysis techniques using descriptive analysis and inferential statistical analysis. It is known that student learning outcomes in the normality test are 0.059, which means that the data is normally distributed, with an average pre-test result of 67.34 and a post-test of 86.71. This is evidenced from the results of the paired sample t-test obtained by a t value of -13.519 with a Sig value. (2-tailed) of 0.000 <0.005 means that there is a significant difference between the pre-test and post-test scores. The n-gain result of 0.61 which is in the medium category indicates that the application of the talking stick learning model assisted by video animation can improve student learning outcomes. Therefore, it is necessary to innovate in learning, such as implementing a fun learning model so that students play an active role and improve learning outcomes.